Hepatic arterial infusion chemotherapy combined with apatinib plus camrelizumab for advanced hepatocellular carcinoma with type Vp4 portal vein tumor thrombosis: a multicenter propensity score-matching analysis - Wu, Shaoteng; Qiu, Feifeng; Zhang, Fengtao; Chen, Pingkang; Zheng, Xiang; Wei, Qiming; Zhang, Haiming; Qian, Cheng; Shu, Ankang; Li, Ming; Xiong, Dejun; Zhong, Sheng (Frontiers in Immunology, 2026)
BackgroundPortal vein main trunk invasion is a serious and difficult complication of hepatocellular carcinoma (HCC), with extremely poor prognosis and limited treatment options. The traditional standard sorafenib has a limited efficacy. The combination of hepatic arterial infusion chemotherapy (HAIC) with camrelizumab and apatinib has shown satisfactory efficacy in previously advanced HCC. Therefore, this approach has potential advantageous survival benefits for HCC with invasion of the portal vein main trunk.MethodsA retrospective review was conducted on the clinical data of advanced HCC patients with type Vp4 portal vein invasion who received HAIC combined with apatinib and camrelizumab (HAICAC group) or HAIC alone (HAIC group) treatment in four medical centers from June 2016 to December 2023. Propensity score matching was employed to balance the baseline differences between the groups. The overall survival, progression-free survival, objective response rate and disease control rate were compared between the groups.ResultsFollowing PSM, the HAICAC regimen demonstrated significantly superior clinical outcomes, with median OS (24.1 versus 7.2 months) and PFS (7.0 versus 4.3 months) significantly exceeding those of HAIC monotherapy (all P<0.001). The combination therapy also exhibited markedly improved tumor response rates, achieving superior objective response rates for both intrahepatic lesions (75.6% versus 31.4%, P<0.001) and PVTT (60.5% versus 17.4%, P<0.001). While the HAICAC group showed a higher incidence of immune-related adverse events compared to the HAIC group, all events were manageable and no grade 5 toxicities occurred.ConclusionFor HCC with Vp4 type PVTT, the combination regimen of HAIC plus apatinib and camrelizumab demonstrates promising efficacy in reducing both intrahepatic tumor burden and thrombus progression, representing a potentially viable treatment approach with an acceptable safety profile.